Comparative analysis of expert evaluation of quality criteria of the educational program for the field of computer-integrated technologies - Gordiyenko, Tetyana; Velychko, Oleh; Salceanu, Alexandru (Видавництво Львівської політехніки, 2023)
The article presents the results of comparative expert research to establish the importance of the applied national criteria for the quality of the educational program (CQEP) of higher education institutions (HEIs). For these studies, a group expert assessment of the importance of the CQEP for the educational program (EP) in the field of computer-integrated technologies was applied. The teaching staff of two universities is involved in conducting such an evaluation: The State University of Telecommunications (Ukraine) and the Gheorghe Asachi Technical University of Iaşi (Romania). To conduct this research, the existing CQEP and their sub-criteria and a special algorithm of group expert evaluation were used. It has been established that the most important CQEP and their sub-criteria include, first of all, CQEP regarding human resources, the educational environment, material resources, and the structure and content of the EP. The greatest spread of experts’ opinions (from the weightiest to the least weighty) can be stated for the sub-criteria of CQEP regarding access to EP and recognition of training results and transparency and publicity. With this in mind, this CQEP sub-criteria requires close attention when revising them for a better balance of the CQEP subcriteria system. Harmonization of the list of fields of knowledge and specialties for which higher education students are trained with the International Standard Classification of Education, as well as the national terminological and conceptual apparatus with the international one, should be considered extremely appropriate in Ukraine. The issue of prioritizing the preparation of higher educational institutions for the accreditation of the EP, meeting the most essential requirements of the sub-criteria of the CQEP, and taking into account their significant number, remains relevant. This also determines the relevance and necessity of conducting special expert studies on the comparison of the importance of CQEP for different fields of knowledge.
Keywords: Computer-integrated technologies; Quality criterion; Educational program; The institution of higher education